There and back again. Examining the development of employee commitment during a prolonged crisis - Rachel E. Gifford; Frank C. van de Baan; Daan Westra; Dirk Ruwaard; Fred R.H. Zijlstra; Lieze T. Poesen; Bram P.I. Fleuren (Elsevier, 2022)
To effectively function and adapt in crises, healthcare organizations rely on the skills and commitment of their workforce. Yet, our current understanding of how employees' workplace commitment is affected by and evolves throughout the course of a crisis remains limited. In this paper, we explore the commitment of hospital staff to an important workplace target, the COVID-19 crisis response, and show how this commitment develops over time. We report on an exploratory case study of hospital staff in a heavily hit region of the Netherlands. We conducted interviews with hospital executives, management, medical and support staff to uncover the issues hospitals faced in recruiting staff to provide COVID-19 care throughout the first and second wave of the crisis. Our findings suggest that while staff initially exhibited high levels of commitment to aiding in the crisis effort, staff were perceived to exhibit lower levels of commitment in the second wave, complicating the provision of COVID-19 care. We unveil three contributing factors to this shift, namely: competing demands, energy depletion and a lack of support and appreciation. Our findings suggest that while staff were initially willing to dedicate themselves and take responsibility for the crisis effort, as their other more stable commitments became more salient in the second wave, their willingness to dedicate limited resources to the crisis effort decreased. In our discussion, we examine the implications of our findings for the literature on workplace commitment, and advance our understanding of employee workplace commitment during crises.